Integrating Ombudsman Principles into Hospital Governance: A Hybrid Accountability Framework for Enhanced Public Trust and Administrative Justice - Muhammad Idris Patarai (CV. Eureka Murakabi Abadi, 2024)
Transparency and accountability have become the cornerstones of modern public governance, particularly in the healthcare sector where administrative justice and patient rights intersect. In Indonesia, the persistent rise of public complaints in healthcare—recorded by the Ombudsman of the Republic of Indonesia as among the highest across public service sectors—reveals systemic gaps between hospital service standards and patient expectations. This study develops an integrative conceptual framework that links Ombudsman principles—independence, impartiality, accessibility, and fairness—with hospital governance and public complaint mechanisms to enhance public accountability and service quality. Drawing upon national regulatory frameworks (Law No. 37/2008) and international literature indexed in Scopus, the research employs a normative–conceptual approach enriched by comparative insights from established healthcare ombudsman systems in the United Kingdom and Brazil. The findings demonstrate that effective integration of Ombudsman principles into hospital governance produces a hybrid accountability system where complaint mechanisms function not merely as reactive tools for dispute resolution but as proactive instruments for systemic learning. Digital analytics tools such as the Healthcare Complaints Analysis Tool (HCAT) and Natural Language Processing (NLP) further strengthen transparency and data-driven oversight, while human-centered communication and ethical intelligence ensure empathy and fairness in complaint handling. The study contributes theoretically by reframing the Ombudsman’s role from a corrective agency to an institutional learning agent within health governance, bridging the gap between administrative justice theory and healthcare management practice. Practically, it offers a model adaptable for low- and middle-income countries to institutionalize justice, trust, and accountability within health systems. The proposed framework positions Ombudsman integration as a pathway toward learning-based governance, where every complaint becomes a catalyst for continuous improvement in public service ethics and hospital performance.